2011
DOI: 10.1007/s10560-011-0244-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the High School Relationship Curriculum Connections: Dating and Emotions

Abstract: Interest in relationship education for high school students has grown since the Deficit Reduction Act of 2005 provided funding for Healthy Marriage Initiative programs. This study used a pretest and posttest design and measures of relationship knowledge and attitudes to evaluate a relationship curriculum taught in required health education classes to a sample of 139 students. Comparison of students' pretest and posttest scores showed slight gains in knowledge about relationships. Analysis based on characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The few studies focusing on relationship education for youth have supported its effectiveness (Adler‐Baeder et al, ; Gardner & Boellard, ; Kerpelman et al, ; Sparks, Lee, & Spjeldnes, ). These studies differ in the outcomes they address, but each finds that participants benefit from exposure to relationship education curricula.…”
Section: The Contents and Function Of Partners/relationships Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies focusing on relationship education for youth have supported its effectiveness (Adler‐Baeder et al, ; Gardner & Boellard, ; Kerpelman et al, ; Sparks, Lee, & Spjeldnes, ). These studies differ in the outcomes they address, but each finds that participants benefit from exposure to relationship education curricula.…”
Section: The Contents and Function Of Partners/relationships Standardsmentioning
confidence: 99%
“…Wadsworth and Markman () encouraged relationship education researchers to search for moderators of the effects of relationship education because no treatment is 100% effective, and moderators can help us understand “what works for whom.” Several studies have explored or proposed moderators of marriage and relationship education in adults (Adler‐Baeder et al, ; Bradford, Adler‐Baeder, Ketring, & Smith, ; Hawkins, Stanley, Blanchard, & Albright, ), but few studies address this topic among teenagers. Most moderator studies (Adler‐Baeder et al, ; Kerpelman, Pittman, & Adler‐Baeder, ; Sparks et al, ) examine the effects of participant characteristics (e.g., gender, race, household income, academic performance, family structure, identity style); however, few examine the effects of treatment‐related factors, though research indicates that one's initial views assessed by pretest scores prior to an educational treatment may affect what one learns from a treatment (e.g., Kerpelman et al, ).…”
Section: The Contents and Function Of Partners/relationships Standardsmentioning
confidence: 99%
“…In addition, a handful of adolescent RE studies (e.g., Antle et al, 2011; Sparks, Lee, & Spjeldnes, 2012) have documented significant change in dating violence acceptance after RE participation. Because unhealthy relationship patterns and dating violence are specifically addressed in RE, positive changes in dating violence acceptance after program participation are expected.…”
Section: Introductionmentioning
confidence: 99%
“…First, regarding participant characteristics (i.e., target and timing), prior research shows that RME may have a greater influence on outcomes for female youth and African American male youth (e.g., Antle et al, ; Bradford et al, ; Kerpelman et al, ; Sparks et al, ). Our findings reinforce similar differences on perceived changes in RRSE.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kerpelman et al (2010) reported greater improvements in conflict management for youth with fewer economic resources or from stepfamilies. Further, studies have found that RME has a greater impact among female than male adolescents for the development of healthier beliefs about romantic relationships, intimacy, and trustworthiness (Kerpelman et al, 2009;Ma et al, 2014) and greater increases in knowledge related to curriculum topics (Sparks, Lee, & Spjeldnes, 2012). Also, Bradford, Erickson, Smith, Adler-Baeder, and Ketring (2014) reported that the greatest increase in positive attitudes toward couples counseling (i.e., "behavioral intentions") after participation in RME occurred among African American female adolescents and Caucasian male adolescents, pointing to the importance of both race and sex.…”
Section: Discussionmentioning
confidence: 99%